PENGARUH PERPUTARAN MODAL KERJA, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Ni Komang Sandra Dewi; I Gusti Ngurah Bagus Gunadi; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The company was founded with the aim of increasing the value of the company so that it can provide prosperity for the owners or shareholders. One of the efforts to achieve its goals, the company always tries to maximize its profit. Many factors can affect the level of profitability of a company. This study aims to analyze the influence of working capital turnover, capital structure, and liquidity variables on the profitability of Food and Beverage companies in Indonesia. The sampling method used purposive sampling, with a sample size of 10 companies. The data analysis used is multiple linear regression analysis. The results showed that the working capital turnover variable had a positive and significant effect on profitability, while the capital structure variable had a significant negative effect on profitability, and liquidity had a negative and insignificant effect on profitability